Introduction to chemical engineering computing - Finlayson, Bruce Alan, 1939- (Hoboken, NJ : Wiley-Interscience, 2006)
Chapter 1: Introduction (p 1-4) Chapter 2: Equations of State (p 5-23) Chapter 3: Vapor-Liquid Equilibrium (p 25-40) Chapter 4: Chemical Reaction Equilibrium (p 41-54) Chapter 5: Mass Balances with Recycle Streams (p 55-71) Chapter 6: Simulation of Mass Transfer Equipment (p 73-88) Chapter 7: Process Simulation (p 89-109) Chapter 8: Chemical Reactors (p 111-146) Chapter 9: Transport Processes in One Dimension (p 147-173) Chapter 10: Fluid Flow in Two and Three Dimensions (p 175-205) Chapter 11: Convective Diffusion Equation in Two and Three Dimensions (p 207-228) Appendix A: Hints When Using Excel® (p 229-238) Appendix B: Hints When Using Matlab® (p 239-258) Appendix C: Hints When Using Aspen Plus® (p 259-268) Appendix D: Hints When Using Femlab® (p 269-291) Appendix E: Parameter Estimation (p 293-306) Appendix F: Mathematical Methods (p 307-322)
Keywords: Matlab; Chemietechnologie